3-D finite element investigation of discrete deadman anchor for earth retaining wall - Chai, Koh Siong (2016)
In the past several years, considerable attention has been given to the ultimate horizontal pull-out resistance of vertical deadman anchors, which are usually used together with earth retaining wall. Unfortunately, no significant effort has been made to understand/study the behaviour of discrete deadman anchor in earth retaining wall (anchored wall) subjected to the deflection of earth retaining wall. Therefore, this research aims to fill up this gap.